FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI KONSUMEN DI SHOPEE DAN TOKOPEDIA - Imari, Iqbal; Abadi, M. Kurnia Rahman; Akbar, Muhammad Ridho (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2024)
The phenomena of internet usage, which is anticipated to grow over time, presents a new economic potential for e-commerce. One of the businesses owned by Pondok Modern Gontor, situated in Ponorogo City, East Java, is La Tansa Gontor Book & Stationery Store which currently also using e-commerce. This study aims to investigate the factors that influence consumer purchase interest in e-commerce used by La Tansa. The Theory of Planned Behavior, popularized by Icek Ajzen, is the theory applied in this study. This hypothesis is predicated on three different variables: behavioral attitude, subjective norms, and perceived behavioral control. In this study, a descriptive survey method is combined with a quantitative approach. With a sample size of 358 participants, the population in this study consisted of the 3,416 followers in marketplace platform. Several linear regression tests were employed in this investigation. A total score of 31,038 indicated that the aspects of product price and quality were thought to be very influential. The product pricing component, one of the two variables included in the study, had the most significant impact on consumer purchasing interest. With a 66.3% percentage. Product quality, on the other hand, has a 11.48% influence on consumer purchasing interest. Overall, the factors of product price and product quality jointly affect consumer purchasing interest with a significance of 0.05 and a F computed value of 293,715 F table 3.021, indicating that both factors have an impact.